1999
DOI: 10.1159/000025679
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose, Not Low-Dose Insulin Increases the Vasoconstrictor Effect of Norepinephrine in Spontaneously Hypertensive Rats: Effects of Antihypertensive Treatment

Abstract: The effect of insulin on the vasoconstriction induced by norepinephrine is presently controversial. Therefore, the aims of our study were: (1) to evaluate the effect of low- and high-dose insulin on the concentration-response curve to norepinephrine in small resistance arteries of spontaneously hypertensive rats (SHR) and Wistar Kyoto rats (WKY) before and after the development of hypertension, and (2) to evaluate the effects of antihypertensive treatment on vascular response to insulin and norepinephrine. Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Our results are partly different in respect to what we have previously observed in an animal model of genetic hypertension (an increased response to norepinephrine in hypertensive rats but not in normotensive ones) [7]. However, in both cases, insulin elicits a prohypertensive effect in pathological conditions (hypertension, diabetes), and not in normal controls.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are partly different in respect to what we have previously observed in an animal model of genetic hypertension (an increased response to norepinephrine in hypertensive rats but not in normotensive ones) [7]. However, in both cases, insulin elicits a prohypertensive effect in pathological conditions (hypertension, diabetes), and not in normal controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, endothelin-1 might be responsible for insulin-induced changes in vascular contractility [40]. In fact, an endothelin-1-mediated increase of the norepinephrine response was previously demonstrated, at least in rats [7]. Finally, as previously mentioned, it is also possible that interactions between insulin and leptin may be impaired in pathological conditions with consequent loss of nitric oxide-induced vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose-dependent effects of insulin on endothelin-mediated vasoconstriction have been reported in arterioles isolated from normal rats during concurrent NOS synthase antagonism (9) and in vascular rings from spontaneously hypertensive rats (43). These observations suggest that a second source of vascular dysfunction may be necessary to demonstrate insulinstimulated vasoconstriction via endothelin.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study has indeed demonstrated that incubation with a high dose (715 nmol/L) but not a low dose (715 pmol/L) of insulin increases the vasoconstrictor effect of NE in resistance vessels of spontaneously hypertensive rats. 35 This effect was attenuated by ET-receptor blockade, suggesting that enhanced NE responses were at least partially mediated by ET. Accordingly, ET-1 has been reported to enhance adrenergic vasoconstriction, 36 suggesting that sympathetic activation in hyperinsulinemic states could be linked to ET.…”
Section: Discussionmentioning
confidence: 96%